Los instrumentos musicales de material reciclable en la concienciación de la conservación del medio ambiente por parte de las niñas y niños del 5to y 6to años de educación básica de la escuela Rosa Grimaneza Ortega de la ciudad de Loja. Periodo 2014-2015 - Ajila Pinzón, Paola Juliana (2016)
Musical Instruments recyclable material awareness for environmental conservation, it is the central idea that part of this work, whose main objective was to contribute to the development of environmental education of students in the 5th and 6th Years Basic Education School "Rosa Ortega Grimaneza" city of Loja, through the construction of musical instruments with recycled material, the universe to investigate it was formedby the director of the institutionwho was applied an interview guide, 7 teachers and 52 studentswho are allocated a survey, giving a total of 60 people, the results showed that 98.1% of the surveyed population, It states that the instruments of recyclable material is a new and innovative alternative, as it helps to raise awareness about the importance of protecting the environment; results that allow us to carry out a proposal that was making musical instruments using recycled materials. It's concluded, the construction of musical instruments with recycled material, help to stimulate the students' commitment to care for the environment in which they live, so teachers and directors of this institution is recommended, consider and use the built musical instruments in the workshop given in the institution, as teaching materials for music class,to thereby confirm that the arts is a means for developing environmental awareness in students.